Accessing HIV treatment and care services in fishing communities around Lake Victoria in Uganda: mobility and transport challenges. Issue 3 (27th September 2019) - Tumwine, Christopher; Aggleton, Peter; Bell, Stephen
Abstract : Qualitative research exploring the influence of community-level factors on access to and use of HIV treatment and care services among people living in fishing communities is limited, especially with respect to those already in receipt of HIV care and on treatment. To enhance understanding of these issues, semi-structured in-depth interviews were conducted with 42 HIV-positive fisherfolk and 15 health care providers from two HIV clinics located in two fishing communities in Uganda. Fisherfolk's mobility and poor transport systems were significant barriers to access to and use of HIV treatment and care. Mobility, which involved regular movement between communities, sometimes led to fisherfolk's inability to access HIV treatment and care. A poor transport system in fishing communities – characterised by irregular transport services and boats in a poor condition – was reported to force both fisherfolk and health care providers sometimes to cancel journeys to centres providing treatment and support. Community-level factors such as these, which relate to the organisation and provision of transport in local community settings, are significant influences on access to HIV treatment and care. Interventions that address these challenges are needed to improve access to and use of HIV treatment and care in fishing communities.